Explore a diverse range of topics and get expert answers on IDNLearn.com. Get thorough and trustworthy answers to your queries from our extensive network of knowledgeable professionals.
Sagot :
To solve this problem, we need to analyze and verify the three given ways of defining a sequence to see if they produce the same sequence or if there is an error in one of them.
1. First Definition: [tex]\( f(x) = 3x + 4 \)[/tex] for [tex]\( x = \{1, 2, 3, \ldots\} \)[/tex]:
- Let's generate the first few terms of the sequence:
- When [tex]\( x = 1 \)[/tex], [tex]\( f(1) = 3(1) + 4 = 7 \)[/tex].
- When [tex]\( x = 2 \)[/tex], [tex]\( f(2) = 3(2) + 4 = 10 \)[/tex].
- When [tex]\( x = 3 \)[/tex], [tex]\( f(3) = 3(3) + 4 = 13 \)[/tex].
- And so on. The sequence generated is [tex]\( 7, 10, 13, \ldots \)[/tex].
2. Second Definition: [tex]\( a_1 = 4 \)[/tex] and [tex]\( a_{n+1} = a_n + 3 \)[/tex] for [tex]\( n = \{1, 2, 3, \ldots\} \)[/tex]:
- Let's generate the first few terms using the recursive definition:
- [tex]\( a_1 = 4 \)[/tex]
- [tex]\( a_2 = a_1 + 3 = 4 + 3 = 7 \)[/tex]
- [tex]\( a_3 = a_2 + 3 = 7 + 3 = 10 \)[/tex]
- [tex]\( a_4 = a_3 + 3 = 10 + 3 = 13 \)[/tex]
- And so on. The sequence generated is [tex]\( 4, 7, 10, 13, 16, \ldots \)[/tex].
3. Third Definition: [tex]\( a_n = 4 + 3(n-1) \)[/tex] for [tex]\( n = \{1, 2, 3, \ldots\} \)[/tex]:
- Let's generate the first few terms using the explicit formula:
- When [tex]\( n = 1 \)[/tex], [tex]\( a_1 = 4 + 3(1-1) = 4 + 3(0) = 4 \)[/tex].
- When [tex]\( n = 2 \)[/tex], [tex]\( a_2 = 4 + 3(2-1) = 4 + 3(1) = 7 \)[/tex].
- When [tex]\( n = 3 \)[/tex], [tex]\( a_3 = 4 + 3(3-1) = 4 + 3(2) = 10 \)[/tex].
- When [tex]\( n = 4 \)[/tex], [tex]\( a_4 = 4 + 3(4-1) = 4 + 3(3) = 13 \)[/tex].
- And so on. The sequence generated is [tex]\( 4, 7, 10, 13, \ldots \)[/tex].
After generating these sequences, we compare them:
1. The first definition generates the sequence [tex]\( 7, 10, 13, \ldots \)[/tex].
2. The second and third definitions both generate the sequence [tex]\( 4, 7, 10, 13, \ldots \)[/tex].
It's evident that the first definition does not match the other two. Therefore, there's an error in the first definition.
Fixing the Error:
- The function [tex]\( f(x) = 3x + 4 \)[/tex] should be adjusted to match the sequences generated by the second and third definitions.
- The correct function appears to be [tex]\( f(x) = 3x + 1 \)[/tex] instead of [tex]\( f(x) = 3x + 4 \)[/tex].
Thus, the correct answer is:
B [tex]\( f(x)=3 x+4 \)[/tex] for [tex]\( x=\{1,2,3, \ldots\} \)[/tex] It should say [tex]\( f(x)=3 x+1 \)[/tex] for [tex]\( x=\{1,2,3, \ldots\} \)[/tex].
1. First Definition: [tex]\( f(x) = 3x + 4 \)[/tex] for [tex]\( x = \{1, 2, 3, \ldots\} \)[/tex]:
- Let's generate the first few terms of the sequence:
- When [tex]\( x = 1 \)[/tex], [tex]\( f(1) = 3(1) + 4 = 7 \)[/tex].
- When [tex]\( x = 2 \)[/tex], [tex]\( f(2) = 3(2) + 4 = 10 \)[/tex].
- When [tex]\( x = 3 \)[/tex], [tex]\( f(3) = 3(3) + 4 = 13 \)[/tex].
- And so on. The sequence generated is [tex]\( 7, 10, 13, \ldots \)[/tex].
2. Second Definition: [tex]\( a_1 = 4 \)[/tex] and [tex]\( a_{n+1} = a_n + 3 \)[/tex] for [tex]\( n = \{1, 2, 3, \ldots\} \)[/tex]:
- Let's generate the first few terms using the recursive definition:
- [tex]\( a_1 = 4 \)[/tex]
- [tex]\( a_2 = a_1 + 3 = 4 + 3 = 7 \)[/tex]
- [tex]\( a_3 = a_2 + 3 = 7 + 3 = 10 \)[/tex]
- [tex]\( a_4 = a_3 + 3 = 10 + 3 = 13 \)[/tex]
- And so on. The sequence generated is [tex]\( 4, 7, 10, 13, 16, \ldots \)[/tex].
3. Third Definition: [tex]\( a_n = 4 + 3(n-1) \)[/tex] for [tex]\( n = \{1, 2, 3, \ldots\} \)[/tex]:
- Let's generate the first few terms using the explicit formula:
- When [tex]\( n = 1 \)[/tex], [tex]\( a_1 = 4 + 3(1-1) = 4 + 3(0) = 4 \)[/tex].
- When [tex]\( n = 2 \)[/tex], [tex]\( a_2 = 4 + 3(2-1) = 4 + 3(1) = 7 \)[/tex].
- When [tex]\( n = 3 \)[/tex], [tex]\( a_3 = 4 + 3(3-1) = 4 + 3(2) = 10 \)[/tex].
- When [tex]\( n = 4 \)[/tex], [tex]\( a_4 = 4 + 3(4-1) = 4 + 3(3) = 13 \)[/tex].
- And so on. The sequence generated is [tex]\( 4, 7, 10, 13, \ldots \)[/tex].
After generating these sequences, we compare them:
1. The first definition generates the sequence [tex]\( 7, 10, 13, \ldots \)[/tex].
2. The second and third definitions both generate the sequence [tex]\( 4, 7, 10, 13, \ldots \)[/tex].
It's evident that the first definition does not match the other two. Therefore, there's an error in the first definition.
Fixing the Error:
- The function [tex]\( f(x) = 3x + 4 \)[/tex] should be adjusted to match the sequences generated by the second and third definitions.
- The correct function appears to be [tex]\( f(x) = 3x + 1 \)[/tex] instead of [tex]\( f(x) = 3x + 4 \)[/tex].
Thus, the correct answer is:
B [tex]\( f(x)=3 x+4 \)[/tex] for [tex]\( x=\{1,2,3, \ldots\} \)[/tex] It should say [tex]\( f(x)=3 x+1 \)[/tex] for [tex]\( x=\{1,2,3, \ldots\} \)[/tex].
Thank you for being part of this discussion. Keep exploring, asking questions, and sharing your insights with the community. Together, we can find the best solutions. IDNLearn.com is dedicated to providing accurate answers. Thank you for visiting, and see you next time for more solutions.